1980
DOI: 10.1259/0007-1285-53-626-107
|View full text |Cite
|
Sign up to set email alerts
|

The relation between radiographic features and determinants of risk of breast cancer

Abstract: Mammograms were obtained from 942 normal women aged over 30 years, and were classified by Wolfe's criteria. In women with an enhanced risk of breast cancer associated with a late age at first child or nulliparity, there was a significant increase in the proportion of P2 and DY mammographic patterns which are thought to be a radiological index of risk. There was a decrease in the proportion of P2 and DY grades in women using steroidal contraceptives. However, the association between radiological and epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…Several other reproductive factors have been reported to be associated with both increased breast cancer risk and greater breast density in pre-and postmenopausal women, including nulliparity, late age at first birth, lower parity, and possibly early age at menarche [25,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. However, in the current study, we found no association between breast density and these breast cancer risk factors, except for parity.…”
Section: Discussioncontrasting
confidence: 71%
“…Several other reproductive factors have been reported to be associated with both increased breast cancer risk and greater breast density in pre-and postmenopausal women, including nulliparity, late age at first birth, lower parity, and possibly early age at menarche [25,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. However, in the current study, we found no association between breast density and these breast cancer risk factors, except for parity.…”
Section: Discussioncontrasting
confidence: 71%
“…A positive association was seen in two studies [16, 18], including a large HMO population of nearly 30,000 women in Seattle [16]. Studies of breast cancer family members [17], Singaporean women [20], and Hispanic women [19] found no association between menarcheal age and breast density.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the influence of age at menarche, which in most studies is inversely related to breast cancer risk [e.g., 13–15], remains uncertain. Some studies have found positive associations [6, 16, 17], at least one suggests an inverse association [18], and others found no relation between age at menarche on breast density [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…The remaining variation in MD is thought to be, in part, genetically regulated (or genetically determined) (reviewed in [6]). Increased MD has been positively associated with family history of breast cancer in most [3, 716], but not all [1721], studies, which have included women with and without a personal history of breast cancer and have used a variety of methods to measure MD. Family studies [22, 23], including studies of sisters [2427] and twins [23, 2729], provide further support for a genetic influence on MD.…”
Section: Introductionmentioning
confidence: 99%